Gamification Elements and GoPay User Retention Among Generation Z in Bandung - Rizkita Sukma Gayanti; Budi Prasetiyo (Penerbit Goodwood, 2026)
Purpose: This study aimed to examine the effect of gamification elements on GoPay user retention among Generation Z in Bandung. The analysis focuses on three core gamification components: the reward system, challenge and mission, and social interaction. Research Methodology: This quantitative study was conducted in Bandung, Indonesia, targeting Generation Z users of the GoPay digital wallet application. Data were collected from 325 respondents using structured questionnaires based on the established literature on gamification and user retention. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4.0 to evaluate the relationships between constructs. Results: The results demonstrated that gamification elements positively influenced user retention. The reward system, challenge and mission, and social interaction significantly affected user satisfaction, loyalty, and usage frequency. The reward system exhibited the strongest effect among the variables. Conclusions: The study concludes that well-designed gamification strategies can enhance user engagement and strengthen the long-term retention of GoPay users, particularly among Generation Z in Bandung. Limitations: This study focused on Generation Z users in Bandung, which restricts the generalizability of the findings to other demographic segments, age groups, or geographic regions. Differences in cultural background, digital literacy, and financial behavior across populations may produce varying outcomes if the model is applied in different contexts. Contributions: This study contributes to the literature on digital marketing and financial technology by providing empirical evidence of the role of gamification in improving user retention. It also offers practical insights for GoPay and other fintech companies in designing effective gamification strategies.